(untitled) (Slavic Studies, 2024)
The purpose of this short article is to provide an analysis of the phenomenon of “dislocated writers” which is taking greater proportions in the third decade of the 21st first century in which we live. Literary artists are beginning to lose their status as cultural and social driving forces, something which was their hallmark primarily in the second half of the twentieth century. The status they hold today is undoubtedly due to, among other factors, the growing globalization, commercialization and the new logic that prevails in the market.